The irrational use of medicinal plants: an integrative review (Research, Society and Development, 2022)
The increase in consumers of natural and medicinal products for prophylaxis and treatment is justified both by its therapeutic potential and by the cost accessibility when compared to industrialized products. However, the irrational use of medicinal plants that follow the formulation of inefficient preparations and erroneous storage of these vegetables can cause great damage to the health of an individual. An integrative review in the databases of the Virtual Health Library, using the insertion of the descriptors in Health Sciences "Phytotherapy" and the term "Irrational use", combined with the help of the Boolean operator "AND", the present study sought to identify medicinal plants used in an irrational way that can pose a risk to the population. From the analysis of the data, synthesized by the review, it was observed that the potentially dangerous medicinal plants verified were: Atractylis gummifera L. , Peganum harmala L., Peganum harmala L., Dittrichia viscosa (L.), Rosmarinus officinalis L., Salvia officinalis L., (Rubiaceae), Peganum harmala L., Papaver somniferum L., Dittrichia viscosa (L.), Anís, Plantago, Duranta repens Linn. (Verbenaceae), Papaver somniferum L., Salvia officinalis L., Artemisia herba-alba Asso., Semenovia suffruticosa, Byrsonima sericea DC. (Malpighiaceae), Duranta repens Linn. (Verbenaceae), Ixora coccinea Linn. (Rubiaceae), Valerian and Chamomile. The results showed that the high dosage of these plants, as well as their association with synthetic drugs can result in toxicity to the patient. Evidencing the role of health professionals, especially pharmacists, in providing information and guidance about the herbal plant used.